Bacterial Contamination of Medical Scissors and Clamps in the Blood Collection Room - Widyaswara, Gravinda; Tulit Ina, Maria Selviana; Tirtana, Arif; Zain, Kumara Rahmawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2025)
Background: Bacterial contamination in blood products can originate from the donor's body or the surrounding environment. Contamination may occur during the blood collection process. Transmission typically happens through the hands and body of the medical personnel, contaminated clothing, medical instruments, and the surrounding environment. Bacterial contamination is a highly influential parameter in indoor air populations, especially in healthcare environments. Objective: The objective of this study was to identify the presence and growth of bacteria on medical scissors and clamps in the blood collection room of the Indonesian Red Cross Sleman Regency. Method: This research employed a descriptive observational method to analyze bacterial growth on scissors and clamps collected from the blood collection room of Indonesian Red Cross Sleman Regency. A cross-sectional approach was used, in which data on potential risk factors were collected at a single point in time. Nutrient Agar (NA) was used as the culture medium in this study. Result: The results of the bacterial isolation indicated that the scissors and clamps in the blood collection room of the Indonesian Red Cross Sleman Regency can be considered sterile, as the number of bacterial colonies did not exceed the normal threshold of <30 colonies. Specifically, 2 bacterial colonies were found on the scissors and 2 on the clamps. Conclusion: The presence of only 2 colonies each on the scissors and clamps suggests that the instruments in the blood collection room of Indonesian Red Cross Sleman Regency are within acceptable sterilization standards.